Moodle E-learning to Improve Motivation and Learning Activities at Green Campus - Koderi; Guntur Cahaya Kesuma (Universitas Pendidikan Ganesha, 2023)
Many students struggle to use e-learning for attendance, interactive lectures, assignment submission, and access to resources and tests. E-learning is said to benefit students in terms of activities and accomplishments. This survey aims to analyze and evaluate the Moodle E-learning role in enhancing motivation and learning activities at Green Campus. A mixed-method method with an explanatory sequential design is used in this investigation. This study included 221 participants. Questionnaires, interviews, and documentation are used to collect data. The statistical regression method was then used to assess the research data. The study's findings indicate that the variable e-learning platform Moodle has a substantial influence on student learning activities at Green Campus. This variable has a major impact on changes in student accomplishment motivation. According to this research, lecturers must make good and fascinating use of the Moodle e-learning platform to boost all activities and student achievement motivation in learning, not just listening activities. Furthermore, universities should be able to ask users to actively participate in developing the design and content of future e-learning developments.